PENGARUH MODEL PBL TERHADAP HASIL BELAJAR IPAS KELAS V SDN 08 PONTIANAK BARAT - Susanti, Efa; Kresnadi, Hery; Ghasya, Dyoty Auliya Vilda (Universitas Tanjungpura, 2026)
This research aims to find out the effect of implementing the problem based learning model on the science and science learning outcomes for class V at SD Negeri 08 West Potianak. The method used in this research is an experimental method with a quasi experimental design. The population in this study was all class V students. Sampling used nonprobability sampling techniques and samples were obtained from class VA as the control class and class VB as the experimental class. The data collection technique uses measurement techniques and the data collection instrument used is a multiple choice test. Based on data analysis, the average posttest score for the experimental class = 77.5 and the average posttest score for the control class = 73.9. The results of hypothesis testing using the t-test with the polled variance formula obtained tcount of 1.481 and ttable (α = 5% and dk = 31 + 30 – 2 = 59) of 0.002, which means tcount > ttable, then Ha is accepted. Based on the results of the effect size (ES) calculation, the ES value = 0.42. Thus it can be concluded that the application of the Problem Based Learning learning model has a moderate influence on the science and science learning outcomes of class V students at SD Negeri 08 West Pontianak by 42%.